Performance studies of VoIP over ethernet LANs - Nizar, Kashif; Sarkar, Nurul I; Hassan, Suhaidi; Wu, Di (Assumption University, Bangkok, Thailand, 2011)
Voice over Internet Protocol (VoIP) is a rapidly growing technology that enables transport of voice over data networks such as Ethernet local area networks (LANs). This growth is due to the integration of voice and data traffic over the existing networking infrastructure, low cost, and improved network management offered by the technology.This research investigates the performance of VoIP traffic characteristics over Ethernet LANs.In the investigation, the impact of increasing the number of VoIP clients, voice codec schemes, and traffic distribution on system performance is considered.Through various simulation experiments under realistic networking scenarios, such as SOHO and campus networks, this study provides an insight into the VoIP performance over Ethernet LANs.The simulation results indicate that all these factors can significantly affect VoIP performance over Ethernet LANs.Under both SOHO and campus network scenarios, increasing the number of VoIP clients, voice packet lengths and different traffic arrival distributions have significant impact on system performance.We preformed our simulation in OPNET simulation tool to validate our experiments.